The Gate of Ki Ranggo Wirosentiko's Grave: Traces of Non-Islamic Cultural Acculturation in the Material Culture Heritage of the Palembang Sultanate - Amilda, Amilda; Holiza, Holiza; Padila, Padila (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
Palembang is known as one of the centers of the Palembang Sultanate. One of the most important cultural relics in Palembang is the Palembang Sultan Cemetery complex. Each of these cemetery complexes has a different architectural shape of the tomb, one of which is the tomb complex of Ki Ranggo Wirosntiko. A Striking distinction in this tomb is the shape of the tomb gate complex building that depicts influences in non-Islam culture. This article will explain the differences in shape in the building of the gate and the influence of non-Islamic culture on the shape of the tomb gate of Ki Ranggo Wirosentiko. The method used is the archeological method using a stylistic analysis of the observation of the ornaments found in the gates of this complex. The results of this study show that the building of the tomb gate of Ki Ranggo Wirosentiko shows acculturation with non-Islamic culture. The profile of the outer gate depicting Hindu influence is marked by the similarity with the stylistic elements in the Bentar temple and Paduraksa Temple, East Java. The resemblance is also visible on the profile of the foot and the mould of the gate resembling the profile found in the Paduraksa Temple. On the profile of the third gate, there is an inscription of the year 1142 H or 1730 M using Arabic letters. The local influence appears on the third gate's appearance, indicating the presence of mustak. Based on the profile of the building of the tomb gate Ki Ranggo Wirosentiko shows the influence of Hindu, Buddhist, Arab, and local cultures on the decorative range of the construction of the grave of the temple.